Risk Factors of Attention Deficit Hyperactivity Disorder in Children - Katayoun Khoushabi; Ameneh Setareh-Forouzan; Shahram Moradi; Parvaneh Mohammadkhani (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: Regarding to ADHD is believed to the most common behavioral disorder in children, the purpose of this study was to investigate the risk factors of Attention Deficit Hyperactivity Disorder in children. This study compared ADHD children and normal children. Materials & Methods: In this comparative study, subjects were 192 children with ADHD who referred to pediatric psychiatric clinic in two years therapeutic period. The children were diagnosed as ADHD according to DSM-IV by two pediatric psychiatrists (experimental group) and 210 normal children who were chosen from schools and day-care centers in Tehran (control group). Research variables were matched with experimental group. Data were analyzed with descriptive methods such as: Q Square test.  Results: Findings showed that 79.3% of ADHD-positive subjects and 54.3% of their controls were boy. Consanguinity of parents, history of ADHD and psychiatric disorders in parents and their relatives and being the first or second child of family were associated with greater risk of ADHD in children and showed significant difference between two groups (P<0.001). Conclusion: Male, Consanguinity marriage, history of ADHD and psychiatric disorders in parents and relatives and the first or second child are risk factors of ADHD.